Phylogeography of two closely related species of Allium endemic to East Asia: Population evolution in response to climate oscillations. Issue 16 (16th July 2018) - Yang, Jingtian; Zhou, Songdong; Huang, Deqing; He, Xingjin
Abstract: This study investigated the effects of climate oscillations on the evolution of two closely related Allium species, A. neriniflorum and A. tubiflorum . We sequenced three cp DNA (cpDNA) fragments ( rps 16, rpl 32‐ trn L, and trn D‐ trn T, together approximately 2, 500 bp in length) of two closely related Allium species, with samples from 367 individuals in 47 populations distributed across the total range of these species. The interspecific and intraspecific divergence times of the two species were in the Quaternary glaciation. The population divergence was high for the cpDNA variation, suggesting a significant phylogeographic structure ( N ST  = 0.844, G ST  = 0.798, p  < 0.05). Remarkable ecological differentiation was also revealed by Niche models and statistical analyses. Our results suggest the speciation event of the two species was triggered by violent climatic changes during the Quaternary glaciation. Abstract : Allium tubiflorum and Allium neriniflorum are two different species based on molecular levels. The divergence time of the two species was estimated at about 2.2 Ma in the onset of the Quaternary glaciation. The intraspecific divergence of A. tubiflorum and A. neriniflorum resulted from the climate oscillation of the largest glaciation in the Quaternary.